The influence of COVID-19 lockdown restrictions on perceived nutrition habits in Rugby Union players - Roberts, C.; Gill, N.; Sims, S. (Frontiers in Nutrition, 2020)
The global outbreak of COVID-19 has led to governments and local authorities implementing nationwide lockdowns in an attempt to encourage social distancing and minimize the spread of the virus. Only essential businesses have been able to remain open, with non-essential businesses and activities either closing or restricting services. With no group training sessions allowed, canceled matches, an inability to work and the closure of eating establishments, Rugby Union players have experienced disruption to their daily lives. Two surveys were distributed among Rugby Union athletes to explore (1) the influence of COVID-19 lockdown restrictions on Rugby Union players' nutrition and training habits and (2) how nutrition habits in New Zealand Rugby Union players change after lockdown restrictions were lifted. In total, 258 respondents completed Survey 1 (84.1% male, 26.4% professional/semi-professional). Of the respondents, 58% indicated they lived with family during lockdown. Total food intake was reported to be higher in 36% of respondents. Fruit and vegetable intake was lower (17%) and packaged/convenience food intake higher (26%) in a minority of respondents. In total, 106 respondents completed Survey 2 (84.9% male, 34.0% professional/semi-professional). Of the respondents, 72% prepared and 67% purchased their own food. Less than half of respondents consumed high-protein food more than twice daily either during or following lockdown. Compared to during lockdown, motivation to train and exercise was greater in 58% of respondents following lockdown. Dieticians and nutritionists within clubs provided most of the nutrition knowledge to athletes however other unreliable sources were identified, such as social media and family members. The ongoing pandemic has presented significant challenges for athletes concerning training and nutrition habits and the current study provides some insight into these. Coaches and performance staff should ensure athletes receive appropriate nutritional and training support whilst being aware of the unique demands the individuals' may face.